Management Foundations for Navigating Ecological Transformation by Resisting, Accepting, or Directing Social–Ecological Change. (17th November 2021) - Magness, Dawn R; Hoang, Linh; Belote, R Travis; Brennan, Jean; Carr, Wylie; Stuart Chapin, F; Clifford, Katherine; Morrison, Wendy; Morton, John M; Sofaer, Helen R
Abstract: Despite striking global change, management to ensure healthy landscapes and sustained natural resources has tended to set objectives on the basis of the historical range of variability in stationary ecosystems. Many social–ecological systems are moving into novel conditions that can result in ecological transformation. We present four foundations to enable a transition to future-oriented conservation and management that increases capacity to manage change. The foundations are to identify plausible social–ecological trajectories, to apply upstream and deliberate engagement and decision-making with stakeholders, to formulate management pathways to desired futures, and to consider a portfolio approach to manage risk and account for multiple preferences across space and time. We use the Kenai National Wildlife Refuge in Alaska as a case study to illustrate how the four foundations address common land management challenges for navigating transformation and deciding when, where, and how to resist, accept, or direct social–ecological change.